Detecção de Brucella canis em cães no município de Cuiabá, através do diagnóstico molecular - Silva, Carla Patrícia Amarante e (2012)
Brucella canis is a zoonosis of public health importance because it is an infectious disease that affects both man and animals. This study aimed to investigate using the technique of Polymerase Chain Reaction(PCR) the occurrence of brucellosis caused by Brucella canis in blood samples in dogs in the city of Cuiabá, State of Mato Grosso, and possible risk factors associated such as sex, race, age and types of management during the period of 2007 to 2008. Three hundred twenty seven samples were analized based on simple random sampling, covering the 04 (four) districts of the city. The occurrence of B. canis was 24.1% (C.I. 95%:19,7- 29,0%). The statiscal analysis showed an association of conjunctivitis (OR of 4.72 (95% CI = 1.30 - 17.76) and p = 0,0103 for Fisher's Exact) and keratitis (OR of 16.69 (95% CI = 1.86 - 385.55) and p = 0,0036 for Fisher's Exact )with the positivity of B. canis. The results of this study demonstrate the occurrence of B. canis and highlights the first-time use as molecular diagnosis of PCR in the city of Cuiabá. The results suggest how good candidate for confirmatory diagnosis of blood samples in dogs to canine brucellosis the molecular diagnosis by PCR.